2010
DOI: 10.1002/pssc.200983497
|View full text |Cite
|
Sign up to set email alerts
|

Crack formation in GaN on Si(111) substrates grown by MOCVD using HT Al‐preseeding and HT AlN buffer layers

Abstract: We have investigated the crack formation in GaN layers grown on Si(111) substrates by MOCVD using an AlN buffer layers and Al‐preseeding process. With an appropriate AlN buffer thickness using optimal TMAl flow rate, we were able to counteract the crack formation usually observed in GaN layers deposited on Si(111) substrate. With a 120 nm thick AlN buffer layer, TMAl source flow rate 18 μmol/min and Al‐preseeding time 5 s, we were able to obtain nearly crack free 2.5 μm GaN surface and a (002) plane HR‐XRD roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Meanwhile, it has been impossible to obtain freestanding GaN wafers grown on a Si substrate because of the large lattice mismatch (16.9%) and the difference between the thermal expansion coefficients of GaN (αa = 5.59 × 10 –6 /K) and Si (αa = 3.77 × 10 –6 /K). These factors impede the growth of freestanding GaN on Si substrates because they lead to formation of cracks and large bowing, owing to a high tensile stress on thick GaN layers grown when the reactor cools from the growth temperature to room temperature after the growth. Moreover, the reaction between Ga and Si due to the out-diffusion of Si atoms into the GaN layers, namely, the meltback effect, renders it even more difficult to obtain freestanding GaN wafers using Si substrates. , Recently, we fabricated and characterized a 2 in. freestanding GaN crystal, 400 μm in thickness and 5 μm in wafer bowing, grown using Si substrates by HVPE, which was achieved by in situ removal of the Si substrate .…”
mentioning
confidence: 99%
“…Meanwhile, it has been impossible to obtain freestanding GaN wafers grown on a Si substrate because of the large lattice mismatch (16.9%) and the difference between the thermal expansion coefficients of GaN (αa = 5.59 × 10 –6 /K) and Si (αa = 3.77 × 10 –6 /K). These factors impede the growth of freestanding GaN on Si substrates because they lead to formation of cracks and large bowing, owing to a high tensile stress on thick GaN layers grown when the reactor cools from the growth temperature to room temperature after the growth. Moreover, the reaction between Ga and Si due to the out-diffusion of Si atoms into the GaN layers, namely, the meltback effect, renders it even more difficult to obtain freestanding GaN wafers using Si substrates. , Recently, we fabricated and characterized a 2 in. freestanding GaN crystal, 400 μm in thickness and 5 μm in wafer bowing, grown using Si substrates by HVPE, which was achieved by in situ removal of the Si substrate .…”
mentioning
confidence: 99%
“…A large number of methods of growing crack-free GaN films with high crystalline quality have been developed. [4][5][6] One of the most effective methods is to employ AlGaN buffer layers between an AlN nucleation layer and a GaN channel layer, 6) which can introduce compressive stress to compensate for the growth tensile stress generated by island coalescence and the cooling down of the wafer from the growth temperature to room temperature. 7) It helps to prevent cracks and improve crystalline quality, which in turn leads to the improved performance characteristics of GaN electronic devices, such as low leakage current and high breakdown voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been done to investigate the thickness of the AlN buffer layer and its effect on the stress and quality of GaN. [5][6][7][8][9] The huge discrepancy between thermal expansion coefficients generates a tensile stress of 1.36 GPa in the in-plane of the GaN film. 10 For the Volmer-Weber film growth of GaN on AlN, coalescence of three-dimensional islands is accompanied by tensile growth stress.…”
Section: Introductionmentioning
confidence: 99%
“…12 Therefore, the tensile stress in the GaN film is hardly counterbalanced completely by a single AlN buffer layer. However, according to J. O. Kim et al, a nearly crack-free 2.5 μm thick GaN film was obtained by optimized AlN layers, 9 and D. K. Kim reported that a 1 μm crack-free GaN film was grown with an 80 nm AlN buffer layer. 8 To illustrate the mechanism of stress relaxation in a GaN film on Si substrate by an AlN buffer layer of varying thicknesses, we systematically studied the crystalline quality of AlN with different thicknesses and its effect on the stress state and quality of GaN on Si.…”
Section: Introductionmentioning
confidence: 99%